2021
DOI: 10.3390/biotech10040020
|View full text |Cite
|
Sign up to set email alerts
|

Searching for G-Quadruplex-Binding Proteins in Plants: New Insight into Possible G-Quadruplex Regulation

Abstract: G-quadruplexes are four-stranded nucleic acid structures occurring in the genomes of all living organisms and viruses. It is increasingly evident that these structures play important molecular roles; generally, by modulating gene expression and overall genome integrity. For a long period, G-quadruplexes have been studied specifically in the context of human promoters, telomeres, and associated diseases (cancers, neurological disorders). Several of the proteins for binding G-quadruplexes are known, providing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
(69 reference statements)
0
6
0
Order By: Relevance
“…In plants, G4 and rG4 motifs appear widespread, but detecting them in vivo remains challenging, and their potential biological roles remain to be better understood (Griffin & Bass, 2018; Liu et al., 2022; Ma et al., 2022; Volnà et al., 2021). It was recently demonstrated that rG4 structures exist in vivo and can act as regulators (Yang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In plants, G4 and rG4 motifs appear widespread, but detecting them in vivo remains challenging, and their potential biological roles remain to be better understood (Griffin & Bass, 2018; Liu et al., 2022; Ma et al., 2022; Volnà et al., 2021). It was recently demonstrated that rG4 structures exist in vivo and can act as regulators (Yang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Human G4‐binding proteins with another motif (RGRGRGRGGGSGGSGGRGRG) called NIKI for “Novel Interesting Quadruplex Interaction” were also found (Brazda et al., 2018). Plant proteins containing GAR or NIKI motifs have been identified and speculated to interact with G4 structures (Volnà et al., 2021). Among them, seven RNA helicases were identified, including DExH1 (Figure S6).…”
Section: Discussionmentioning
confidence: 99%
“…Many G4-binding proteins in animals and humans are known [ 43 ]. Recently, it has been shown that proteins in barley seedlings can bind to PQSs and form DNA–protein complexes [ 44 ], so we can expect that G4-binding proteins also will be present in plant genomes [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The motif-binding potential of G-quadruplexes having vital roles in gene regulation was done by using a plant model organism "Arabidopsis thaliana (Thale cress)". 17 Research studies on Hordeum vulgare (Barley) clearly state that the DNA-binding proteins in barley seedlings are rich in potential G-quadruplexes, although the genome is rich in i-motifs. 18 .…”
Section: Discussionmentioning
confidence: 99%